Techno-Economic Analysis of Fuel Vehicles as Logistic Distribution Facilities in Indonesia by Considering the Carbon Emission Cost - Saputri, Virda Hersy Lutviana; Hisjam, Muhammad (International Journal of Energy Economics and Policy, 2018)
This study aims to perform a techno-economic analysis for the investment of the Vigas usage as substitution for Pertamax 92 fuel that is starting to be rare. The assessment is done by calculating the value of BEP, NPV, IRR, and PP. In addition, this study also calculates the amount of carbon emission costs that must be incurred by the company when using Pertamax fuel 92 and Vigas. The analyzed pollutants are CO, HC, NOx, and CO2. Based on the calculation results, BEP from replacement Pertamax 92 to Vigas can be achieved at the distance of 22.653.43 km. The value of NPV, IRR, and PP indicates that the investment is feasible to be realized. In addition, the cost of carbon emissions generated by Vigas is lower than Pertamax 92, with a difference of IDR 4,191,482.73. Keywords: carbon emission, fuel vehicle, techno-economy analysis JEL Classifications: L52, O25, Q42 DOI: https://doi.org/10.32479/ijeep.6933